Faktor-Faktor Yang Memengaruhi Individu Untuk Memilih Karir Sebagai Akuntan Pajak - Dimas Adi Purwanto; Amir Hidayatulloh (AKUNTANSI 45, 2024)
This study aims to analyze the factors that influence the choice of career as a tax accountant. This population is a tax brevet (training) participant at a tax consulting agency in the Special Region of Yogyakarta, while the sample of this study is a tax brevet (training) participant at a tax consulting agency in the City of Yogyakarta. Samples were taken using convenience sampling technique. Analysis of the research data using linear regression analysis with the help of the SPSS tool. This study obtains the result that career choice to become a tax accountant is influenced by tax training and tax knowledge. However, the career choice of becoming a tax accountant is not influenced by self-motivation